Antimicrobial Screening of Venpoosani Nei (Benincasa Hispida Medicated Ghee) - A Siddha Herbal Formulation - Kavitha.T,; Arunadevi.R,; Susila.R,; Usha.A,; Ganesan.R,; Esaivani.S, (International Journal of Pharma and Bio Sciences, 2020)
Antimicrobial agents are essential in reducing the universal burden of infectious diseases. The increasing alarm of antibiotic resistance, as well as the evolution of new strains of disease causing agents, necessitates the development of new antimicrobial agents against resistant pathogens. Siddha medicine is one of the most established traditional systems comprising of copious formulations that can defend against various pathogens. Venpoosani nei is a compound herbal drug with Benincasa hispida fruit extract act as one of its major ingredient. Though it has been indicated in Siddha formulary of India, Part-1for treating pitha diseases caused due to excessive heat in the body such as gynaecological infections and urinary tract infections, it still lacks evidence with scientific data. Therefore, this study was focused on exploring the antimicrobial properties of Venpoosani nei by agar well diffusion method using Mueller-Hinton Agar for bacterial strains such as Escherichia coli and Klebsiella pneumoniae and Sabaroud’s dextrose agar for fungi Candida albicans. Antimicrobial activities of fractions of Ven poosani nei, ranging from 25µl to 100µl along with 25µl of the standard solution were used for the assessment. The study results revealed the efficacy of Venpoosani nei as an intermediate antimicrobial agent as per the Clinical and Laboratory Standards Institute. The results of the present study ensures that Venpoosani nei is a potent Siddha formulation towards the management of genitourinal infections especially in females.